Associations Between Leisure Physical Activity and Mathematics Interest: A Longitudinal Analysis - Yuhuan Zhang; Lidong Wang; Tian Li; Xiao Ma (SAGE Open)
Previous studies have indicated a positive association between physical activity (PA) and mathematics achievement. The present study explored the association of PA outside school with math interest using longitudinal data from Kaifeng, a medium-sized city in Central China. A two-tier multilevel logistic model was conducted using 2,132 students’ math test scores, self-reported PA frequency, and math learning-related experience in December 2019 and January 2021. Socioeconomic status, school location, and sex were all controlled. The results showed that physical exercise frequency and physical exercise per class outside school had a significant positive impact on mathematics interest ( β = 0 . 072 , p = 0 . 001 ; β = 0 . 153 , p = 0 . 043 ), as did previous mathematics interest ( β = 0 . 581 , p = 0 . 000 ) and self-educational expectation ( β = − 0 . 232 , p = 0 . 033 ; β = − 0 . 432 , p = 0 . 000 ). It indicated that regular physical exercise outside of school can lead to increased mathematics interest.